The perception of the public towards the involvement of illegal immigrant in criminal activities in Kota Kinabalu / Norfa Aizan Ismali and Rozeliana David - Ismali, Norfa Aizan; David, Rozeliana (2015)
The title of our research or study is about the perception of the public towards the involvement of illegal immigrant in criminal activities in Kota Kinabalu. We interested to do this research title is to investigate the public perception towards the illegal immigrants issue, criminal activities, and the factor that influence their perception including their experiences, level of studies as well as media reports that they get or read from. Additionally, in Malaysia the Government has set up many Royal Commission inquiries to solve the dispute, issues and unsolved case in the country. For the issue of illegal immigrants, the Government bodies that responsible with this issues including Immigration Department, Police Department and others. Recently in 2012, the Government of Malaysia has passed the issues of illegal immigrants in Sabah to the Royal Commission which they gather information about the issue. However, there is no other alternative to solve the illegal immigrants in Sabah was set up by the Government itself. From the data gather from the public around Kota Kinabalu city, the Government can make alternatives to curb the problem faced by the people especially regarding to the illegal immigrants involvement in criminal activities in Sabah. By having this study the public itself can determine their level of their perception based on their experience, level of knowledge and media reports which have been given in the television, newspaper and many more.